GLICOMANANO ESTERIFICADO EM RAÇÕES PARA FRANGOS CONTENDO MILHO OU SORGO EXPERIMENTALMENTE CONTAMINADAS POR FUNGOS OU COM AFLATOXINA B1 - ROCHA, Fernanda Rodrigues Taveira (2009)
Two experiments were conducted with 960 Cobb 500 chicks raised in battery heated to 21 days. In the first experiment, birds were fed diets with corn and sorghum non-musty and moldy, or not treated with the mycotoxin adsorbent based glicomanano ester (GME) at concentrations of 0 and 0.1% of the diet. The experiment was conducted in a completely randomized in a 2 x 2 x 2 (x grain quality x adsorbent) and five replicates of 12 birds each. For the second experiment, we used four doses of aflatoxin B1 (0, 0.5, 1.0, 2.5 ppm of AFB1) and the same concentrations of GME in a completely randomized in a 4 x 2 (doses of AFB1 x concentrations GME). Diets isonutrient from corn or sorghum and soybean meal meeting the nutritional requirements proposed by the Brazilian tables. We evaluated the weight gain, feed intake, feed conversion and digestibility of dry matter (DM), ether extract (EE) and protein (N) in two metabolic tests conducted 4 to 7 and 17 to 21 days of age, for the first experiment and a test for the second aged between four and seven days. We also assessed the biometry of lymphoid organs and digestive systems, the production of antibodies against the vaccine virus disease Newcatle and histological evaluation of the bursa of Fabricius and liver. Statistical analysis was performed by GLM procedure of SAS  and Tukey (5%) to compare the means in the case of variable performance and metabolism and other variables the data were described. Chickens fed moldy grains not perform better, regardless of the inclusion of mycotoxin adsorbent for. For grains contaminated with fungi, the additive improved the digestibility and retention of nutrients, especially fat, the main substrate for the development of this organism. Moldy grains decreased the development of the organs of the digestive system and did not affect the organs of the lymphoid system and vaccine response, but it altered the histological structure of the organs evaluated. The histological damage was reduced by GME in the bursa and liver. The AFB1 affected the performance of chickens and GME did not reverse the deterioration in performance, but the effects on digestibility were minimized, especially for fats. The presence of AFB1 interfered with the development of lymphoid organs and digestive systems, depressed the response of poultry vaccination and the onset and increased severity of lesions in the liver and bursa of Fabricius, but with the use of GME, the intensity of effect in body of the birds was lower